2020
DOI: 10.21203/rs.3.rs-52493/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Nuclear Receptors (NRs) Genes have Prognostic Significance in Hepatocellular Carcinoma Patients

Abstract: Background: Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related mortality in the world. Human nuclear receptors (NRs) have been identified to closely related to various cancer. However, the prognostic significance of NRs on HCC patients has not been studied in detail.Method: We downloaded the mRNA profiles and clinical information of 371 HCC patients from TCGA database and analyzed the expression of 48 NRs. The consensus clustering analysis with the mRNA levels of 48 NRs was performed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…HCC comprises 75-85% of liver cancers and has a poor prognosis [1]. Some studies have shown multiple genes present good predictive potential in assessing HCC prognosis [15][16][17][18]. Recently, the importance of ICI therapy in HCC patients has been proven.…”
Section: Discussionmentioning
confidence: 99%
“…HCC comprises 75-85% of liver cancers and has a poor prognosis [1]. Some studies have shown multiple genes present good predictive potential in assessing HCC prognosis [15][16][17][18]. Recently, the importance of ICI therapy in HCC patients has been proven.…”
Section: Discussionmentioning
confidence: 99%
“…The R Circos package was used to map the change in 10 CRRGs on 23 pairs of chromosomes to investigate the relationships between CRRG copy number and chromosome. The differential expression of these CRRGs in TCGA-LUAD was compared using the Wilcoxon rank-sum test in the limma package, which provides a comprehensive solution for microarray and RNA-Seq differential analyses (13). A waterfall plot was created using the maftools package of R to bear out the mutation rate of CRRGs in patients with LUAD.…”
Section: Differential Expression Of Crrgsmentioning
confidence: 99%
“…We have conducted extensive literature study to verify these regulatory relationships. For example, the lncRNA FAM99A has been found to be up-regulated in HCC and closely related to clinical prognosis (Sun et al, 2020). There is increasing evidence that lncRNA GAS5 acts as a tumor suppressor, which is downregulated in certain tumor tissues and combined with miRNA to regulate related signaling pathways (Cheng et al, 2018).…”
Section: Regulatory Network Of Immune-related Hub Genesmentioning
confidence: 99%
“…CREB1 has been reported to be related with metastasis, tumor stage and poor outcome in gastric cancer (Wang et al, 2015), and the knockdown of CREB1 could inhibit liver cancer cell migration (Yang et al, 2013). PPARD has been reported to accelerate colorectal tumorigenesis, progression, and invasion (Liu et al, 2019), it could effectively predict the prognosis of HCC patients as an independent prognostic signature (Sun et al, 2021). It has been reported that hsa-miR-122-5p levels are connected with cholesterol levels in a viral hepatitis-free human population and associate with fatty liver and lipoprotein metabolism (Raitoharju et al, 2016).…”
Section: Regulatory Network Of Immune-related Hub Genesmentioning
confidence: 99%